2020
DOI: 10.1016/j.xkme.2020.05.011
|View full text |Cite|
|
Sign up to set email alerts
|

Nephron Number and Time to Remission in Steroid-Sensitive Minimal Change Disease

Abstract: Rationale & Objective The response to corticosteroid therapy may differ among patients with minimal change disease (MCD). Previous studies have suggested that glomerular hypertrophy or low areal glomerular density in biopsy specimens, which may be related to fewer nephrons, is associated with such a difference. We examined the associations between nephron number and the therapeutic response to corticosteroids in patients with MCD. Study Design Retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…48,49 By dividing the total nephron GFR by the total number of nonsclerotic (functioning) glomeruli in both kidneys, SNGFR was estimated and several factors were identified that possibly influence the SNGFR in healthy subjects, including obesity. 50 Recently, Sasaki et al 51,52 further modified this method and established a regression equation model to estimate the kidney cortical volume by measuring kidney parenchymal volume using unenhanced CT images in human beings. Evaluation of cortical volume by this method has allowed estimation of total glomerular number per kidney in patients with kidney disease who often are not suitable candidates for image analyses using contrast media.…”
Section: Pathophysiology Involved In Obesity-associated Kidney Impairment Intrarenal Hemodynamic Changes and Single-nephron Glomerular Hymentioning
confidence: 99%
“…48,49 By dividing the total nephron GFR by the total number of nonsclerotic (functioning) glomeruli in both kidneys, SNGFR was estimated and several factors were identified that possibly influence the SNGFR in healthy subjects, including obesity. 50 Recently, Sasaki et al 51,52 further modified this method and established a regression equation model to estimate the kidney cortical volume by measuring kidney parenchymal volume using unenhanced CT images in human beings. Evaluation of cortical volume by this method has allowed estimation of total glomerular number per kidney in patients with kidney disease who often are not suitable candidates for image analyses using contrast media.…”
Section: Pathophysiology Involved In Obesity-associated Kidney Impairment Intrarenal Hemodynamic Changes and Single-nephron Glomerular Hymentioning
confidence: 99%
“… 18 This technical advancement enabled us to estimate the SNGFR in patients with kidney disease, for which the administration of contrast media is generally contraindicated. 19 21 In this study, we aimed to assess single-nephron parameters, including SNGFR and single-nephron urinary protein excretion (SNUPE), in patients with MN with different Ehrenreich and Churg (EC) stages for GBM lesions.…”
Section: Introductionmentioning
confidence: 99%
“…MCD is the most frequent glomerulopathy leading to the NS in childhood, accounting for about 70-90%, while adult MCD accounts for 10-20% [3,4]. Most MCD patients are responsive to corticosteroids therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There is still a lot of evidence that they are different manifestations of the same progressive disease [2]. MCD is the most frequent glomerulopathy leading to the NS in childhood, accounting for about 70-90%, while adult MCD accounts for 10-20% [3,4]. Most MCD patients are responsive to corticosteroids therapy.…”
Section: Introductionmentioning
confidence: 99%